Pulmonary diffuse large B-cell lymphoma with concurrent organizing pneumonia: a case report - Xiaofeng Lu; Dekun Zhou; Li Zou; Guoqi Zhou (Frontiers in Medicine)
Primary pulmonary lymphoma represents an uncommon extranodal manifestation of non-Hodgkin lymphoma, with atypical clinical and radiographic features frequently leading to diagnostic challenges. Herein, we present a rare case of a 56 years-old female who presented with recurrent pyrexia. Initial thoracic computed tomography (CT) demonstrated a mass-like consolidation in the left lower lobe with bilateral pulmonary nodules. Transbronchial biopsy established organizing pneumonia; however, underlying malignancy could not be excluded. Following high-dose prednisolone therapy, clinical improvement was observed with corresponding radiographic resolution. Upon corticosteroid discontinuation, febrile recurrence developed with CT demonstrating bilateral pulmonary lesion progression. Repeat bronchoscopy revealed endobronchial lesions, though biopsy demonstrated only atypical cellular features without definitive diagnosis. Six months after initial presentation, cervical lymphadenopathy developed, and excisional lymph node biopsy confirmed diffuse large B-cell lymphoma. Following four cycles of standard R-CHOP chemotherapy with RECIST criteria assessment, partial radiographic response of pulmonary lesions was documented. This case represents a documented coexistence of primary pulmonary DLBCL and organizing pneumonia, offering unique insights into diagnostic challenges and therapeutic implications.